Radicalism and Religious Texts Understanding - Haidary, Abdullah Haq Al; Fauzi, Ahmad; Taufiq, Muhammad (KALAM, 2020)
This research is a response to radical thinking in the name of religion. Some radical groups use the arguments of the religious text as reinforcements for acts of terrorism that have spread in several areas. This paper aims to dismantle the methodology of interpreting the verses of the al-Qur’an which are often used as justification for violence in the name of religion. This research is a qualitative research and this type of research is literature research by discussing books, both from primary and secondary books related to the theme being studied. The steps in this research are to explain the meaning and history of radicalization and deradicalization, collect verses of the Qur’an that are often interpreted radically, and explain the misinterpretations that have been widely politicized towards radical thinking. This article finds that there are two things that cause radicalism. first, there is a reduction in religious understanding due to ignorance and an incomplete understanding of religious texts. second, textual-normative understanding of religious texts. This article concludes that understanding religious texts (al-Qur'an and Hadith) requires a strong scientific basis. Radicalism arises because of the textual-normative method of understanding that often loses the substance of the text. As a result, his religious understanding becomes counter-productive to the spirit of Islam which is rahmatan lil alamin.